Submission to the Inquiry by the Director of Liquor Licensing into proposed restrictions on the sale of packaged liquor in Port Hedland and South Hedland - Gray, Dennis; Saggers, S. (2002)
This report has been prepared, on behalf of the Executive Director Public Health, Department of Health, for presentation at an Inquiry to be held, under Section 64 of the Liquor Licensing Act (1988), at South Hedland Court on the 18th and 19th June 2002. The purpose of the inquiry is to: hear evidence and submissions in relation to the proposed restrictions on the twelve licensees authorised to sell packaged liquor in Port Hedland and South Hedland (Director of Liquor Licensing 21st May 2002a).The proposed restrictions, which are to apply from Sunday to Friday, for a 12 month trialperiod, are as follows.1. The sale of up to one block of packaged low strength beer (eg: 30 cans) (3.5% alcohol by volume of less) per customer may be sold between the hours of 10.00am and 10.00pm.2. The sale of full strength packaged liquor shall not commence before 12 noon and cease no later than 10.00pm. During these trading hours, the sale of liquor will be subject to the following limits on the volume of liquor that may be sold per customer. 4.5 litres of full strength beer or UDLs (eg: 12 cans); or 2 litres of wine; or 700ml of spirits.3. Normal trading conditions will apply on all Saturdays during the trial period.The Director of Liquor Licensing has invited evidence from interested parties regarding:(i) the extent of alcohol-related harm in the two towns;(ii) potential adverse effects of proposed restrictions;(iii) key issues;(iv) complementary measures;(v) suggestions for alternative proposals (Director of Liquor Licensing 2002b).